The effect of exercise accordance the impulse intraday index to development the explosive power of the legs index to accelerate the starting a 100-meter freestyle - Amanh, Mohammed (Journal of Physical Education, 2015)
The research aims to develop the explosive power of the legs and starting to accelerate the 100-meter freestyle with training in accordance with the impulse Index intraday. The problem with research work on the use of exercises according to the intraday impulse in the development of the explosive power of the legs and the index starting to accelerate, and the 100-meter runners. The researcher found that the exercises of the payment according to the intraday positive influence in the development of some physical abilities and variables Kinematic and accomplish ran 100 meters to the research sample, and this is consistent with the imposition of the search. The researcher recommended the importance of the adoption of the impulse Index intraday rationing exercises in the speed of the young runners